The acoustic repertoire of wild common bottlenose dolphins (Tursiops truncatus) in Walvis Bay, Namibia - Gridley, T.; Nastasi, A.; Kriesell, H.J.; Elwen, S.H. (Bioacoustics (Berkhamsted), 2015)
Describing the repertoire of sounds produced by wild cetaceans is necessary for understanding their function, for acoustic population monitoring and for measuring the potential influence of anthropogenic impact. Geographic variation in the types and parameters of sounds makes regional assessment of vocal behaviour necessary. We describe the acoustic repertoire of a small population of common bottlenose dolphins (Tursiops truncatus) inhabiting Walvis Bay, Namibia from recordings made over 59 encounters (72 h) between 2009 and 2012. The characteristics of burst pulse (BP) sounds, low-frequency narrow-band (LFN) sounds, brays, whistles and chirps are described. The BP sounds identified were generated at 150-1050 pulses per second, and most were short, lasting less than 1 s in duration. Bottlenose dolphins from Walvis Bay produce the lowest frequency LFN sounds described for the species. Whistles ranged in frequency from 1.58 to 23.24 kHz, and the mean acoustic parameters were within the range of those described from other geographic regions. Chirps were identified infrequently and usually as single occurrences. Although several sound types were often produced in close temporal succession, we found little evidence of stereotyped bray production, even during recordings of animals feeding. Our results demonstrate geographic variation in both the characteristics and sound types used by bottlenose dolphins and highlight the importance of regional data collection as a pre-curser to passive acoustic monitoring programmes.